Turismo, tiempo libre y desarrollo rural - Aguilar, Juan; de Frutos, Francisco; Pascau, Modesto; Gracia, Miguel Angel (Acciones e Investigaciones Sociales, 2013)
Turismo, tiempo libre y desarrollo rural